Nematic calamitic bisazobenzene liquid crystal: synthesis and mesomorphic properties of 1-methoxybutyloxy-4`-(4-phenylazo)azobenzene - Ab. Rahman, Mohamad Zaki; Abdbakar Salisu, Abusalam; Silong, Sidik; Rahman, Md Lutfor; Ahmad @ Ayob, Mansor (Knowledgia Review, Malaysia, 2009)
A new calamitic liquid crystal material with rod-shape bisazobenzene moieties as a core has been synthesized and characterized by spectroscopic methods. The mesomorphic properties were investigated by differential scanning calorimetry and polarizing optical microscopy. The rod-shaped molecule 1- methoxybutyloxy-4’-(4-phenylazo)azobenzene was prepared by diazotization of 4-phenylazoaniline, coupling with phenol and subsequent etherification of 1-Bromobutyloxy-4’-(4-phenylazo) azobenzene in methanol. The presence of nematic mesophase was confirmed by the textures.